KAJIAN PSIKOLOGI LINTAS BUDAYA TENTANG STRES PENGASUHAN PADA IBU - Nurussakinah Daulay (JURNAL TARBIYAH, 2016)
Positive parenting spend with their children is indispensable in influencing their development. Especially the role of mothers in foster emotional closeness of mother and child attachment relationship. Parents (especially mothers) are directly involved in the caring of children throughout the day. The amount of burden felt by the mother as the closest figure in parenting as well as a figure who must work outside the home to help the family's economic costs, these conditions can be stressful parenting. Conditions of stress and negative emotions will cause the mother's mother's experience of delay in the parenting process. It would be bad in parenting because of stress and negative emotions are often experienced by the mother behaves is not healthy, not positive and will exacerbate the situation of children, such as child neglect even violent behavior toward his son. The importance of the mother also has been studied, including by Gray (2003) that there was evidence suggesting that the burden of parenting more weight falls on mothers than fathers (Moes, Koegel, Schreibman & Loos, 1992 (in Marshall & Long, 2010) , and the mother will suffer more emotionally the load (Gray, 2003, in Marshall & Long, 2010).Keywords: Mother, stressors, negative emotions, parenting stress